Analysis of the PRK family of Rho GTPase effector proteins in the context of cell cycle progression and epithelial morphogenesis - Magalhães, Ana (2010)
Tese de doutoramento, Biologia (Biologia Celular), Universidade de Lisboa, Faculdade de Ciências, 2010